Identification of treatment elements for adolescents with callous unemotional traits: a systematic narrative review - Pamela M. Waaler; Josefine Bergseth; Linda Vaskinn; Kristin Espenes; Thale Holtan; John Kjøbli; Gunnar Bjørnebekk (BMC, 2024)
Abstract Adolescents with callous unemotional (CU) traits are at risk for poor quality-of-life outcomes such as incarceration, suicide, and psychopathy. It is currently unknown which treatments are implemented with CU adolescents specifically and which elements make up these interventions. A narrative systematic review was used to identify the treatments and common elements used with CU adolescents (12-18 years). Eligible studies were randomized controlled trials and quasi-experimental studies evaluating psychosocial interventions, delivered within a clinical context, and directed towards the adolescent or their family. Eight studies with 1291 participants were included. Significant decreases in CU traits were demonstrated only in a minority of studies. The most utilized practice elements were set goals for treatment, practice interpersonal/communication skills, prepare for termination, and teach parents skills and strategies; the most utilized process elements were formal therapy, practice exercises, important others, and flexible/adaptive. A majority of the studies did not report an implementation element. While theoretical frameworks for CU children are employed with CU adolescents, there is still uncertainty regarding their suitability for this age group. Given the limited empirical evidence, there is a critical need for further exploration.